Flow forming of aluminum alloy rim from cast preform - Yang, Yun (2016)
This report reflected the study on flow forming process with liquid forged aluminum alloy Al6061 with 97.92% Al, 0.6% Si, 0.28% Mn, 1.0% Mg and 0.2% Cr. [4] The pre-form of the flow forming process comes from the liquid forging which is also known as squeeze casting or liquid metal forging where the solidification of the melt occur under pressure. The target rim profile came from 3D scanning. The tooling design, the profile of the pre-form and the paths of the flow process was analyzed and modified by finite element method (FEM) on Abaqus CAE 6.14. With five simulation results, the design and paths were finalized. Next, experiments on formability of liquid forged aluminum alloy Al6061 were done. To simplify the test, a cylinder with diameter 36mm and height 45mm is formed by liquid forging process instead of the complete pre-form. The effect of pre heat treatment on formability in cold flow forming was investigated. The effect of different feed rate on flow forming process was studied. The tensile tests were done to verify the strength and ductility of the liquid forged Al6061 in hot forming and cold forming with or without heat treatment. The formability of cold forming and hot forming process was analyzed. After all the analysis was finished, the parameters for flow forming process on the pre-form with scaled down size of actual rim was finalized. During the last flow forming experiment, the rim was formed successfully. The microstructure and harness value of different part of the rim was studied.